2013
DOI: 10.1021/nl403566u
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy Observation of TiO2 Nanocrystal Evolution in High-Temperature Atomic Layer Deposition

Abstract: Understanding the evolution of amorphous and crystalline phases during atomic layer deposition (ALD) is essential for creating high quality dielectrics, multifunctional films/coatings, and predictable surface functionalization. Through comprehensive atomistic electron microscopy study of ALD TiO2 nanostructures at designed growth cycles, we revealed the transformation process and sequence of atom arrangement during TiO2 ALD growth. Evolution of TiO2 nanostructures in ALD was found following a path from amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 41 publications
5
59
0
Order By: Relevance
“…4,16,17 The majority of fundamental studies on ALD is, in fact, concerned with the surface chemistry behind the deposition of the atoms of choice on a given substrate, and far less research has been devoted to the understanding of the diffusion phenomena underlying the formation of NPs and the evolution of their PSD. 4,1621 As a result, ALD of NPs has been reported with different PSDs, and the growth mechanisms leading to these different PSDs are still under debate. 1,2,4,12,14,17,2023 …”
mentioning
confidence: 99%
“…4,16,17 The majority of fundamental studies on ALD is, in fact, concerned with the surface chemistry behind the deposition of the atoms of choice on a given substrate, and far less research has been devoted to the understanding of the diffusion phenomena underlying the formation of NPs and the evolution of their PSD. 4,1621 As a result, ALD of NPs has been reported with different PSDs, and the growth mechanisms leading to these different PSDs are still under debate. 1,2,4,12,14,17,2023 …”
mentioning
confidence: 99%
“…However, most of the synthesized ALD materials are limited to polycrystalline and amorphous. [271] Thus, in order to understand and grow single crystalline materials with desired morphology and phase, surface chemistry may not be the only consideration. [270] Meanwhile, a modified high-temperature ALD process has also been used to yield anisotropic 1D TiO 2 crystal nanorods, but the growth behavior is not obeying the layer-by-layer growth model.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…Inspired by a recent finding, 23 Wen and He 24 posed the question: “Can oriented attachment be an efficient growth mechanism for the synthesis of 1D nanocrystals via ALD?” Oriented attachment is a nonclassical growth mechanism, mostly observed in the liquid phase, that involves the self-organization of particles or crystallites that migrate, align, and then fuse along a preferential crystallographic orientation, such that the resulting crystal grows in an asymmetric fashion. 2527 Although still poorly understood, a growing body of evidence suggests that oriented attachment dominates the solution-based growth not only of important nanomaterials but also of minerals in biogenic and geological environments.…”
Section: Introductionmentioning
confidence: 99%
“…25,2830 For this reason, De Yoreo et al 28 argued that a rational exploitation of oriented attachment can bring about significant advances in the design and synthesis of nanomaterials. Along these lines, Shi et al 23 have shown that high-temperature (≥600 °C) ALD of TiO 2 can indeed be used to grow NRs via a mechanism that the authors argued to be a vapor-phase variant of oriented attachment. In fact, in contrast to the oriented attachment of individual crystals that align and fuse, they proposed that the NRs grow at the expense of an amorphous layer encapsulating the lateral facets, which migrates and attaches onto the facets exposed to the gas phase.…”
Section: Introductionmentioning
confidence: 99%